2020
DOI: 10.1111/1467-923x.12892
|View full text |Cite
|
Sign up to set email alerts
|

Researching Fact Checking: Present Limitations and Future Opportunities

Abstract: The fact checking field has grown tremendously in the past decade, as has academic interest in the practice, with dozens of studies testing the effectiveness of corrections. However, research on fact checking is not yet optimised to help fact checkers address the global challenges of mis‐ and disinformation. In this paper, we review the literature on fact checking’s effects and identify two key gaps. First, we discuss the limited diversity and external validity of existing studies, which have overwhelmingly be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 18 publications
(18 reference statements)
0
17
0
2
Order By: Relevance
“…Where the continued influence effect refers to the general continued use of corrected misinformation in memory and reasoning, belief regression is the temporal impermanence of the correction's efficacy. The vast majority of misinformation research examines belief change immediately after corrections have been presented (Dias & Sippitt, 2020), despite longer-term belief change being more relevant to the real world. Studies that include a delayed retention interval have found belief regression to be a robust phenomenon (Carey et al, 2022;Berinsky, 2017;Rich & Zaragoza, 2020), although its mechanisms remain unknown.…”
Section: Memory Failure Predicts Belief Regression After the Correcti...mentioning
confidence: 99%
“…Where the continued influence effect refers to the general continued use of corrected misinformation in memory and reasoning, belief regression is the temporal impermanence of the correction's efficacy. The vast majority of misinformation research examines belief change immediately after corrections have been presented (Dias & Sippitt, 2020), despite longer-term belief change being more relevant to the real world. Studies that include a delayed retention interval have found belief regression to be a robust phenomenon (Carey et al, 2022;Berinsky, 2017;Rich & Zaragoza, 2020), although its mechanisms remain unknown.…”
Section: Memory Failure Predicts Belief Regression After the Correcti...mentioning
confidence: 99%
“…The discussion of the validity of existing studies on fact-checking and their present limitations has been the aim of a recent review [46] that complements most of the literature reviews on fake news [47][48][49][50].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the plethora of automated systems and tools available for fact-checking, our understanding of their usefulness in practise is limited. Furthermore, there is a dearth of scholarly work that engages with the limitations of the current fact-checking tools and practices ( [60,82] are a few exceptions). Our paper addresses this gap by interviewing the various stakeholder groups involved in the fact-checking process to understand the technological infrastructure supporting their work including the tools that are actually used by the stakeholders in practice, limitations of the current tools and the challenges faced by multiple stakeholder groups.…”
Section: Current Landscape Of Computational Research In Fact-checkingmentioning
confidence: 99%